A review of 20 years of human papillomavirus research in Slovenia - Poljak, Mario (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2011)
Background: Human papillomaviruses (HPV), remarkably diverse DNA viruses etiologically linked with various benign and malignant neoplastic lesions of mucosal and skin epithelium have been the subject of intensive research for the last 30 years worldwide. Objective: Briefly to review 20 years of HPV research in Slovenia by analyzing the articles published in journals indexed in peer-reviewed databases Medline/Pubmed, Science Citation Index/Web of Science, Embase and PsycINFO. Methods and results: Up until October 2011, Slovenian researchers published 73 articles in journals indexed in peer-reviewed databases, which can be divided into 15 categories: detection ofHPV in archival clinical specimens, development of novel HPV tests, evaluation of various commercial tests for the detection of high- and low-riskalpha-HPV, HPV and anogenital tumours, HPV testing in routine gynecological practice, HPV and laryngeal benign tumours, HPV and laryngeal epithelial hyperplastic lesions and laryngeal cancer, HPV and tumors in oral cavity, HPV and esophageal benign and malignant tumors, HPV and inverted papillomas, genomic diversity of selected HPV types, hair follicles as an important endogenous reservoir of HPV, identification and characterization ofnovel HPV types, HPV vaccination and HPV basic research. Until October 2011,Slovenian HPV papers received 473 citations (self-citation excluded) and their Hirsch index is currently h=13. Conclusion: In the last 20 years, Slovenian HPV researchers have been actively and successfully incorporated in the international HPV community and have contributed small but significant achievements in the field.
Keywords: Anus Neoplasms; Anus, novotvorbe; Bolezen, rezervoarji; Classification; Databases, Bibliographic; Disease Reservoirs; Esophageal Neoplasms; Genital Neoplasms, Female; Ginekološke novotvorbe; Grlo, novotvorbe; Hair Follicle; infekcije; Isolation And Purification; Laryngeal Neoplasms; Lasni mešiček; Mouth Neoplasms; Papillomavirus, Human; papiloma virusi; Papilomavirus človeški; Periodicals; Periodika; Polimerazna, verižna reakcija; Polymerase Chain Reaction; Požiralnik, novotvorbe; Publishing; Slovenia; Slovenija; Usta, novotvorbe; Viral Vaccines; Virusna cepiva; Založništvo; Zbirke podatkov bibliografske